Optimalisasi Pelayanan Pengisian Bahan Bakar Menggunakan Simulasi Monte Carlo Pada SPBU di Kota Mataram - Aria Fauzi; Amrullah Amrullah; Nani Kurniati (Indonesian, 2020)
Good quality service for refueling fuel oil (BBM) at gas stations was vital for today's society. However, the service quality at gas stations has not been known until now. One of the gas stations that were strategic in Mataram city, namely SPBU 54.832.03 on Jl. Majapahit Pagesangan. One of the factors affecting the quality of gas station services is the availability of the number of dispensers that services customer at the gas station. Therefore, the research of the optimal gas station service's optimal condition was based on the number of dispensers of fuel. We use the distribution of arrival times of customers and service times at the gas stations. On the observation, we use two kinds of fuel dispensers, namely the dispenser of Premium and Pertalite for the motorcycle. The Monte Carlo simulation method shows that the optimal number of dispensers for the SPBU is three nozzles for Premium dispensers and 4 for Pertalite Motorcycle dispensers.